2023
DOI: 10.21037/tcr-23-1190
|View full text |Cite
|
Sign up to set email alerts
|

Do alkaline phosphatases have great potential in the diagnosis, prognosis, and treatment of tumors?

Tingting Jiang,
Qun Zeng,
Jun He

Abstract: Alkaline phosphatase (ALP) is a group of enzymes that catalyze hydrolysis of phosphate esters at an alkaline pH, resulting in the generation of inorganic phosphate. These enzymes are widely distributed, and their activity is found in various tissues including bone, liver, intestine, and placenta. However, abnormalities in ALP expression and activity have been observed in certain types of cancer. In some cases, elevated serum levels of ALP are observed in patients with liver and bone metastasis. In other cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 87 publications
(147 reference statements)
0
0
0
Order By: Relevance
“…Moreover, an inverse correlation was observed between the levels of ALP and the ovarian cancer biomarker CA125. In several cancer types, including colorectal cancer (CRC), breast cancer, and non-small cell lung cancer (NSCLC), low levels of alkaline phosphatase (ALP) have been associated with a worse prognosis for patients [ 28 ]. Some studies have observed a relationship between low ALPL expression and chemo-resistance of high-grade serous ovarian cancer (HGSOC) cells to paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an inverse correlation was observed between the levels of ALP and the ovarian cancer biomarker CA125. In several cancer types, including colorectal cancer (CRC), breast cancer, and non-small cell lung cancer (NSCLC), low levels of alkaline phosphatase (ALP) have been associated with a worse prognosis for patients [ 28 ]. Some studies have observed a relationship between low ALPL expression and chemo-resistance of high-grade serous ovarian cancer (HGSOC) cells to paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fast increases over time and overall elevated trajectories of CRP have also been found to be predictors of high risk of progression (Riedl et al 2020 ). While research on ALP has demonstrated their potential as biomarkers across different tumour types, its role in NSCLC remains uncertain (Jiang et al 2023 ), and literature concerning NSCLC patients receiving immunotherapy is limited. Yang et al ( 2023 ) found that higher levels of pre-treatment ALP are associated with lower overall response rate, and shorter median progression-free survival (mPFS) in patients with NSCLC treated with immune checkpoint inhibitors and that ALP is an independent prognostic indicator of mPFS.…”
Section: Discussionmentioning
confidence: 99%
“…Its activity has been demonstrated in cytoplasmic droplets, which raises the hypothesis that ALPL catalyzes dephosphorylation and transport of phosphate groups between the epididymal sperm and epididymal fluid. ALPL might be a potential biomarker for prostate and testicular cancer [ 39 ]. This enzyme inhibitor can reduce the growth and invasion of cancer cells [ 39 ].…”
Section: Protein Markersmentioning
confidence: 99%
“…ALPL might be a potential biomarker for prostate and testicular cancer [ 39 ]. This enzyme inhibitor can reduce the growth and invasion of cancer cells [ 39 ]. Measurement of the enzymatic activity of ALPL in the canine seminal plasma has been used for the diagnosis of incomplete ejaculation or azoospermia in dogs [ 38 ], and a reduced concentration of ALPL in the seminal plasma suggests bilateral obstruction of the vas deferens or epididymis [ 40 ].…”
Section: Protein Markersmentioning
confidence: 99%